Specialized properties of the triceps surae muscle-tendon unit in professional ballet dancers - Moltubakk, M. M.; Magulas, M. M.; Villars, F. O.; Seynnes, O. R.; Bojsen-Møller, J. (Scandinavian Journal of Medicine & Science in Sports, 2018)
This study compared professional ballet dancers (n=10) to non-stretching controls (n=10) with the purpose of comparing muscle and tendon morphology, mechanical, neural and functional properties of the triceps surae and their role for ankle joint flexibility. Torque-angle and torque-velocity data were obtained during passive and active conditions by use of isokinetic dynamometry, while tissue morphology and mechanical properties were evaluated by ultrasonography. Dancers displayed longer gastrocnemius medialis fascicles (55 ± 5 vs 47 ± 6 mm) and a longer (207 ± 33 vs 167 ± 10 mm) and more compliant (230 ± 87 vs 364 ± 106 N·mm-1) Achilles tendon compared to controls. Greater passive ankle dorsiflexion range of motion (40 ± 7 vs 17 ± 9°) was seen in dancers, resulting from greater fascicle strain and greater elongation of the muscle. Peak electromyographic (EMG) activity recorded during passive stretching was lower in dancers, and at common joint angles, dancers displayed lower EMG amplitude and lower passive joint stiffness. No differences between groups were seen in maximal isometric plantar flexor torque, isokinetic peak torque, angle of peak torque or work. In conclusion, the greater ankle joint flexibility of professional dancers seems attributed to multiple differences in morphological and mechanical properties of muscle and tendinous tissues, and to factors related to neural activation.